Импульсная катодолюминесценция вольфрамсодержащих материалов - Корепанов В. И. Владимир Иванович; Лисицына Л. А.; Лисицын В. М. Виктор Михайлович; Тимошенко Н. Н.; Тупицина И. А. (2011, 2011)
Заглавие с экрана